PERBANDINGAN AKTIVITAS FISIK JENIS AEROBIK DAN ANAEROBIK TERHADAP KADAR HIGH DENSITY LIPOPROTEIN (HDL) - David pakaya; Eka Mutiara Herman (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2023)
Physical activity is classified based on biochemically process of energy shynthesis into aerobic and anaerobic physical activity. These activities has the ability to increase the High Density Lipoprotein (HDL) on body. The aim of this study is to determine the comparison between aerobic and anaerobic physical activity on HDL levels. This is a quasi experimental research with pre and post test design. This study partisipant used purposive sampling methods, totally 60 individuals, were divided into two groups, that is aerobic physical activity group and anaerobic physical activity group. Data of HDL levels were perform used Cholesterol Oxidase – Peroxidase Aminoantypirin (CHOD-PAP) methods. Data as a pair for measured the increased of HDL leves in two groups and analyzed with GrapPhad Prism 8.0.0 used the Unpaired t-test. In This study we found hhe HDL levels on the aerobic and anaerobic physical activity showed a significant increased (p<0,0001). The comparison on HDL levels between aerobic and anaerobic physical activity showed a non-significant difference (p=0,7740). in the conclusion, The aerobic and anaerobic physical activity has effect on increased the HDL levels, but has no difference when compared between the aerobic and anaerobic physical activity on increased HDL levels.